Relationship of Self Control with Nomophobia in School-Age Children in 1st Nguling Public Elementary School Pasuruan Regency - Putri Ayunda Retno Arini; Lantin Sulistyorini; Peni Perdani Juliningrum (Nursing and Health Sciences Journal (NHSJ), 2021)
Self-control is an internal resource used to regulate individual behavior. Therefore, school-age children with a lack of self-control potentially experience a tendency to become dependent on smartphones, which makes them feel anxious when they are away from their smartphones (Nomophobia). This study aimed to analyze the correlation between self-control and Nomophobia on school-age children at SDN Nguling 1 Pasuruan Regency. Furthermore, this study used a descriptive analitic research design with a cross-sectional approach conducted on seventy-seven samples under the inclusion criteria with a random sampling technique. The questionnaires used in this research were the Self-Control questionnaire and Nomophobia questionnaire. The self-control and Nomophobia correlation analysis used a Chi Square statistic test, with a significance level of 0.05. The result showed that 33.8% (twenty-six respondents) had good self-control and 66.2% (fifty-one respondents) had poor self-control. Fifty-two respondents (67.5%) experienced Nomophobia, while twenty-five respondents (32.5%) did not experience Nomophobia. There was a significant correlation between self-control and Nomophobia (p = 0.023 and OR = 0.319).